2022
DOI: 10.3390/ma15196571
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of the Process Parameters in Electric Discharge Machining of 316L Porous Stainless Steel Using Metaheuristic Techniques

Abstract: Electric discharge machining is an essential modern manufacturing process employed to machine porous sintered metals. The sintered 316L porous stainless steel (PSS) components are widely used in diverse engineering domains, as interconnected pores are present. The PSS material has excellent lightweight and damping properties and superior mechanical and metallurgical properties. However, conventional machining techniques are not suitable for porous metals machining. Such techniques tend to block the micro-pores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Table 4 analysis reveals that individual output responses optimize at different input variable levels. Due to this particular situation, it is necessary to conduct multi-objective optimization to collectively optimize the manufacturing output [ 53 , 54 , 55 , 56 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Table 4 analysis reveals that individual output responses optimize at different input variable levels. Due to this particular situation, it is necessary to conduct multi-objective optimization to collectively optimize the manufacturing output [ 53 , 54 , 55 , 56 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…This intensified thermal effect contributes to the gradual increase in wear rate observed. Additionally, higher discharge currents can lead to more frequent and intense electrical discharges between the electrode and the workpiece, causing greater mechanical erosion and material displacement, further contributing to wear [39]. However, unlike Brass and Copper electrodes, Ti-6Al-4V-SiCp electrodes possess unique properties such as the presence of the Ti 3 SiC 2 phase, which enhances their high-temperature resistance.…”
Section: Electrode Wear Ratementioning
confidence: 99%
“…14 A regression model using desirability function analysis (DFA) was also used to optimize the MRR of Ti64 alloy, and it was observed that the applied current (I) and P off are the main variables affecting MRR during the WEDM process. 15 Stainless steel alloys are also studied by many researchers and different optimization techniques like Taguchi signal-to-noise analysis, 16 GA, 17 DFA, 18 PSO 19 , and others are used for performance optimization during the WEDM process. The Taguchi signalto-noise analysis was used to optimize the WEDM of a 316 stainless steel-clad surface.…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel alloys are also studied by many researchers and different optimization techniques like Taguchi signal-to-noise analysis, 16 GA, 17 DFA, 18 PSO 19 , and others are used for performance optimization during the WEDM process. The Taguchi signal-to-noise analysis was used to optimize the WEDM of a 316 stainless steel-clad surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation